Advancements in Sustainable Design for Scooters, Autos, and ‎Passenger Cars: A Lifecycle Analysis - Salwadkar , Mrunal; Mishra, Namrata (International Journal of Basic and Applied Sciences, 2025)
This research explores developments in sustainable vehicle design to reduce environmental impacts across passenger cars at different life ‎cycle phases. The research highlights three key points, including the selection of sustainable materials, productive energy optimization, and the execution of recycling programs. Lifecycle analysis highlights future development through recycled content, with renewable ‎energy modularity and lightweight design to minimize resource usage and carbon emissions. Biodegradable polymers provide sustainable motion systems for scooters alongside solid-state batteries for electric vehicles and hybrid solutions for standard cars. The use of ‎emerging technologies that include smart features such as IoT sensors and energy optimization is recognized as a key method for operational ‎enhancement. The research establishes that vehicle sustainability should be attainable across all product life stages until the final scrap using ‎various sustainable lifecycle principles. New hi-tech materials must be both affordable, and the current battery recycling processes remain ‎restricted. This research provides valuable insight to manufacturers, along with policy-makers and scholars, who now understand that sustainable ‎innovations enable automotive industries to enter circular economies at minimal environmental cost‎.